The effect of political neuromarketing 2.0 on election outcomes: The case of Trump's presidential campaign 2016 - Hegazy, Islam Mohamed (Review of economics & political science : REPS, 2021)
Purpose The purpose of this paper is the better understanding of the increasing relation between big data 2.0 and neuromarketing, particularly to influence election outcomes, along with a special aim to discuss some raised doubts about Trump's presidential campaign 2016 and its ability to hijack American political consumers' minds, and to direct their votes. Design/methodology/approach This paper combines deductive/inductive methodology to define the term of political neuromarketing 2.0 through a brief literature review of related concepts of big data 2.0, virtual identity and neuromarketing. It then applies a single qualitative case study by presenting the history and causes of online voter microtargeting in the USA, and analyzing the political neuromarketing 2.0 mechanisms adopted by Trump's political campaign team in the 2016 presidential election. Findings Based on Trump's political marketing mechanisms analysis, the paper believes that big data 2.0 and neuromarketing techniques played an unusual role in reading political consumers' minds and helping the controversial candidate to meet one of the most unexpected victories in the presidential elections. Nevertheless, this paper argues that the ethics of using political neuromarketing 2.0 to sell candidates and its negative impacts on the quality of democracy are and will continue to be a subject of ongoing debates. Originality/value The marriage of big data 2.0 and political neuromarketing is a new interdisciplinary field of inquiry. This paper provides a useful introduction and further explanations for why and how Trump's campaign defied initial loss predictions and attained victory during this election.